Smart substation secondary equipment plug and play technology application. Issue 5 (January 2021) - Tang, Zhijun; Lin, Guodong; Chao, Wujie; Zhai, Bolong; Liang, Yi; Xu, Jie
Abstract: Is proposed in this paper, including the design of intelligent substation, construction and operational stages within the whole life cycle of technology innovation, further analysis the secondary equipment key problems and techniques of modular design, to "plug and play" technology system research and the application in the smart substation as the main line, the paper introduces the construction stage in prefabricated tank secondary equipment standardization of interface design, this paper discusses the operational phase process layer intelligent device plug and play, avoid setting of relay protection and automatic recognition of intelligent tripping and migration research such as technology protection function. The construction period of the substation is greatly shortened, and the intelligent control is realized to "plug and play".